Autophagy and antipsychotic treatment response: Characterising a potential relationship in a neuropsychiatric disorders context - Lagerwall, Jessica (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.